VILLAGE ECONOMIC DEVELOPMENT STRATEGIES THROUGH BUMDES FROM AN ISLAMIC ECONOMIC REVIEW - Kromsian, Marice (International Journal of Social Service and Research, 2024)
This study uses a qualitative descriptive approach with a case study on BUMDes Muda Jaya Mandiri in Benyom Jaya 1 Village in Nimbokrang District, Papua. The researcher used qualitative analysis techniques to outline the data obtained through interviews, observations, and document analysis. The results show that the community has not fully felt optimally the benefits produced in the BumDes, only a few people feel the benefits, it depends on the field results managed by the BUMdes or the results obtained are uncertain. The application of Islamic economic principles can provide insights into achieving social welfare goals.